WHAT DRIVES PURCHASE DECISIONS OF CUT FLOWER CONSUMERS? - Dzokoto, J. G.; Obeng-Sarkodie, K.; Badu-Prah, C. (UDS International Journal of Development, 2018)
Notwithstanding the benefits of and prospects for consumption of cut flowers, the low consumption and the dearth in the literature on the drivers of cut flower purchase decisions in some developing countries, necessitated the identification of the reasons for non-purchase of cut flower and the drivers of cut flower purchase decisions. Using fractional regression modelling and selecting the cauchit link function based on battery of empirical tests some findings were made. Lack of interest, inadequate knowledge, and high prices of cut flowers are reasons for non-purchase of cut flowers. Monthly income, roses, redbronze and yellow coloured cut flowers drive cut flower purchase decisions. These results call for prioritising roses, with more red coloured flowers for sale. The need for producers and sellers to minimise production cost and put up competitive product prices are recommended. Finally, the selection of the cuachit link function in the binary choice modelling suggests the need to explore link functions other than probit and logit link functions. Keywords: Binary models, cuachit, cut flowers, ornamentals, purchase decision